INFLUÊNCIA DE PROTETORES FÍSICOS COLORIDOS NAS TROCAS GASOSAS EM MUDAS DE CANAFÍSTULA [ Peltophorum dubium (Spreng.) Taub.] - Klein, Jeferson; Rampim, Leandro; Kestring, Débora; Guimarães, Vandeir Francisco; Rodrigues, João Domingos (Universidade Federal de Santa Maria, 2016)
ABSTRACT The utilization of physical protectors has been considered an efficient technique for direct sowing of different species, mainly native ones. Based on the importance of the species Peltophorum dubium for revegetation of degraded areas, tree planting and landscaping, this study evaluated gas exchanges in canafistula seedlings under the influence of physical protectors subjected to different luminosity rates. The experiment was carried out in pots a Dystropheric Red Latosol, a typical soil of the study region. Seedlings of Peltophorum dubium were evaluated at 30, 50, 70, 90, 110, and 130 days after sowing (DAS). Thus, the following treatments were adopted: T1, absence of physical protector (APP); T2, transparent physical protector (TPP); T3, transparent physical protector + blue cellophane (BPP) and T4, transparent physical protector + red cellophane (RPP). The evaluated characteristics were: stomatal conductance, transpiration, CO2 assimilation, CO2 concentration inside the substomatal chamber and water use efficiency. In general, all types of physical protectors led to higher mean values of gas exchanges during their permanence in the sowing site until 70 DAS, except for CO2 assimilation. However, water use efficiency was higher in APP seedlings at the same period.

RESUMO A utilização de protetores físicos é uma técnica eficiente na semeadura direta de espécies nativas. Devido à importância da espécie Peltophorum dubium para a utilização no repovoamento de áreas degradadas, arborização e paisagismo, determinou-se o comportamento fisiológico das plantas com a análise da influência de um protetor físico com diferentes taxas de luminosidade no processo das trocas gasosas das plantas. O experimento foi conduzido em vasos com o solo Latossolo Vermelho Distroférrico, típico da região, em vasos com solo. As plantas de Peltophorum dubium foram avaliadas aos 30, 50, 70, 90, 110 e 130 dias após a semeadura (DAS) com os tratamentos: T1, ausência de protetor físico (APF); T2, protetor físico transparente (PFT); T3, protetor físico transparente + celofane azul (PFA) e T4, protetor físico transparente + celofane vermelho (PFV). Foram avaliadas as seguintes características: condutância estomática, transpiração, assimilação de CO2, concentração de CO2 no interior da câmara subestomática e eficiência do uso de água. Os resultados obtidos mostraram que o protetor físico independentemente de sua coloração promoveu aumento dos valores médios de trocas gasosas durante a permanência dos protetores físicos no ponto de semeadura 70 DAS, exceto para assimilação líquida de CO2. No entanto, a eficiência do uso de água foi maior com APF 70 DAS.
INFLUENCE OF COLORED PHYSICAL PROTECTORS ON GAS EXCHANGES OF CANAFISTULA [Peltophorum dubium (Spreng.) Taub.] SEEDLINGS
Keywords: Stomatal conductance; transpiration; CO2 assimilation; water use efficiency; condutância estomática; transpiração; assimilação de CO2; eficiência do uso de água